ASSET BASED COMMUNITY DEVELOPMENT DI PESANTREN WISATA: IMPLEMENTASI STRATEGIS DI PP. AN-NUR 2 AL MURTADLO MALANG - Djawahir, Abdillah Ubaidi (Universitas Islam Raden Rahmat Malang, 2018)
This paper aims to explore the Asset Base Community Development (ABCD) on the implementation of the pesantren community, focusing on seven specific principles. Induction deduction design, including in-depth interviews, Focus Group Discussion (FGD), workshops, observations, and document analysis, were used. Findings of